Second Law Analysis Of Gas Based Thermal Power Plant To Improve Its Performance. - H.Chandra, A.Arora, M.K.Pal*, (International Journal of Scientific Research and Management (IJSRM), 2017)
To examine the degradation of energy during a practice, the production of entropy, and loss of work opportunities exergy is analyzed. This analysis provides an alternative plan to ensure superior performance of a power plant.Exergy analysis is carried out for URAN Gas based thermal power plant (Bokadvira Maharashtra) by conducting mass, energy and exergy analysis of each component in the gas turbine power plant. Parametric analysis of various factors like compression ratio ( , compressor inlet air temperature (AT), Turbine inlet temperature (TIT), on irreversibility of each and every component of Gas Turbine plant is carried out. The paper addresses how the fluctuation in cycle temperature influences the exergetic efficiency and exergetic destruction in the plant. The rate of exergy destruction in Turbine is about 5.2% whereas that in combustion chamber was about 36.4%, According to the result of study, the combustion chamber and Turbine are found to be chief means of irreversibility’s in the plant. It is also found that the exergetic efficiency and exergy destruction are dependent on alteration of turbine inlet temperature.